College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.4 - Average Rate of Change of a Function - 2.4 Exercises: 11

Answer

(a) 3 (b) 3

Work Step by Step

We are given: $f(x)=3x-2$, $x=2,x=3$ (a) We calculate the net change: $f(3)-f(2)=[3*3-2]-[3*2-2]=7-4=3$ (b) We calculate the average rate of change: $\displaystyle \frac{f(3)-f(2)}{3-2}=\frac{3}{1}=3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.